Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam (Chemical Communications, 2016)
Biuret-modified tetraamidomacrocyclic cobalt complex [Co-III-bTAML]- is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O-2. Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co-V(O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.